Qualitative indicators of sperm bulls of spermogonial jsc "krasnoyarskugol" - Chetvertakova, Е V; Abaza, Y V (Mongolian Journal of Agricultural Sciences, 2018)
Sperm quality is one of the most important criteria for bull manufacturer is used in the mode of the sperm donor was a. On spermatogenesis can affect both genotypical and paratypical factors. The quality of sperm is determined by ejaculate volume, concentration, sperm motility and morphology.